Consequences of self-medication in renal insufficiency patients (Research, Society and Development, 2021)
Self-medication refers to the consumption of medication to treat diseases and symptoms, resulting from a self-assessment, without the participation of a physician or qualified professional. This practice, despite being understood as part of self-care, when negligently performed represents a great risk. The effects of this practice can cause from drug interactions and adverse reactions, to severe cases of intoxication leading to death. Therefore, this study aims to verify the rates of self-medication in patients with renal failure, describe its consequences, analyze its main causes and the importance of the pharmacist's role in this context. This is an exploratory and descriptive research with a quali-quantitative approach, carried out from august to october 2021. Data collection was carried out through the application of an online, closed, structured, self-applied and anonymous questionnaire, whose model is inserts in snowball technique. Subsequently, an analysis and construction of a table with pre-defined parameters was carried out, as well as a discussion of the results obtained, as well as a correlation with studies available in the literature. The results revealed that the rate of self-medication in patients with renal failure is high. It is concluded that the rate of kidney patients who self-medicate is high, and that this practice can negatively affect the treatment of these patients. Furthermore, the insertion of the pharmacist was essential to reduce self-medication and improve quality of life, contributing to a safer treatment and adoption of a more adequate and effective drug therapy.